Study on Decentralized Internet (Trinity Journal of Management, IT & Media (TJMITM), 2022)
When a node or user is trying to communicate on the internet with other user  or a user which is using a service or tool without involving any third party .i.e.  which controls your data and involving the usage of the concepts like peer-to peer network, distributed web technologies, protocols and applications to make  the internet more open and accessible is called Decentralized Internet. It directly  contrasts with the centralized internet, the de facto internet of today, which  is mainly controlled by a few large tech companies. These tech giants wield an  enormous amount of power, acting as gatekeepers by determining and enforcing  policies for their users. The research paper explains about Centralized Internet,  Decentralized Internet and its protocols, Applications, Uses, and Difference  between Centralized Internet & Decentralized Internet and Security Protocols  Used in Decentralized Internet.
Keywords: Network; Protocols; Decentralized; Centralized; Internet; Websites; Servers